PENGEMBANGAN MEDIA PEMBELAJARAN ARITMATIKA SOSIAL BERBASIS ROLE PLAYING GAME BERBANTUAN MACROMEDIA FLASH PROFESSIONAL 8 - Nur Saidah; Dita Riska Nurputri; Nani Ratnaningsih (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2022)
This study aims to determine the feasibility of using mathematics learning media in-based Social Arithmetic materials Role Playing Game with the help of theapplication Macromedia Flash Professional 8. The method used in this study is themethod Research and Development using the ADDIE development procedure (Analysis, Design, Development, Implementation, and Evaluation). Methods of data collection using questionnaires, interviews, and expert validation. The results of data analysis in the media validation process include media experts, namely 4.83 meaning "good", material experts 4.8125 meaning "good" and user feasibility analysis 4.28 meaning "good". In order to obtain an overall average of the results of reviews expertand the user of the media that is developed is equal to 4.55 are included in both categories. Based on the results of the review by the expert, this learning media is declared feasible to be implemented in a fun learning process for students